Revision of the African horntail genus Afrotremex (Hymenoptera: Siricidae) - Goulet, Henri (Zootaxa, 2014)
Afrotremex is one of ten extant genera of Siricidae, known as horntails or woodwasps. Species are restricted to the central forested regions of Africa. Their biology and economic significance are unknown. However, the host of one species, A. xylophagus, is known. Their larvae are wood-boring insects. The genus consists of six species: Afrotremex hyalinatus (Mocsáry), A. violaceus Pasteels, A. comatus Goulet, n. sp., A. opacus Goulet, n. sp., A. pallipennis Goulet, n. sp., and A. xylophagus Goulet, n. sp. The genus is characterized, its phylogenetic placement is discussed, and a key to species is provided. For each species (if pertinent), the following are included: synonymy, diagnosis, comparative diagnosis, description, type material, origin of specific epithet, taxonomic notes, and range.